The Role of BMT NU Ngasem Jampet Branch in Increasing MSME Income in Jampet Market Through Rahn Financing - Wahyudi, M. Eko; Purnomo, Joko Hadi; Muctharom, Moch. Zaenal Azis (University of Darusssalam Gontor, 2021)
The purpose of this research was to describe the role of BMT NU Ngasem Jampet Branch in increasing the income of MSMEs in Jampet Market through Rahn Financing. The method used was qualitative. The results showed that the role of financing applied by BMT NU Ngasem Jampet Branch is in accordance with the objectives of Islamic financial institutions in general, namely improving the quality of the community’s economic business for the welfare of the community and its members. Especially in financing products, because the existence of this financing makes it a solution for MSMEs or market traders in the capital used to develop and improve their business than before. So that financing is one way for MSMEs or market traders to increase their business income. The success of BMT NU Ngasem Jampet Branch in carrying out work programs related to financing realized for MSMEs or market traders. This is evidenced by the implementation of financing carried out by BMT NU Ngasem Jampet Branch with several MSMEs or traders in Jampet Market who carry out financing totaling 22 members, but there are some members who have difficulty in terms of installments because their sales are still quiet unlike other traders. So that it makes the installments delay and makes the installment time longer. Meanwhile, members who experience business development and are smooth in financing installments and make the repayment time according to maturity. From the application of financing to 11 MSMEs in the Jampet Market, there was an increase in income for rahn financing with an average of 3.4% of income per month of May 2021.